Versatility of the Anterolateral Thigh Flap for Abdominal Wall Reconstruction - Nadine E. Pedrazzi, MD; Riccardo Schweizer, MD; Holger J. Klein, MD; Stephan Steiner, MD; René Vonlanthen, MD; Thomas Hermanns, MD; Didier Schneiter, MD; Pietro Giovanoli, MD; Jan A. Plock, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Abdominal wall reconstruction represents an ambitious and demanding challenge. This study aimed to illustrate the versatility of the anterolateral thigh (ALT) flap in its different designs for the reconstruction of complex defects of the abdominal wall. Methods:. Charts of patients with complex abdominal wall defects who underwent a reconstruction with an ALT flap at the University Hospital of Zurich (2018–2020) were reviewed retrospectively. Patient characteristics and ALT flaps used were analyzed in detail. Results:. Ten patients received a total of 12 ALT flaps. Free flaps were applied to defects in the upper third of the abdomen. All flaps were harvested with a fascial component. An iliotibial tract reinforcement was incorporated in 4 (33%) cases, and 1 case included a muscular component and motor nerve, to provide functional reconstructive potential. A total of 30% of cases experienced complications requiring surgical revision during a mean follow-up of 5 months. Conclusions:. The ALT flap represents a workhorse in abdominal wall reconstruction due to its versatility and anatomical proximity. Depending on the localization of the defect, this flap can be used in a pedicled or free microsurgical manner. The fascial component of the ALT fasciocutaneous flap and of the extended iliotibial tract provides stable fascia for reinforcement or fascial reconstruction of the abdominal wall. Raised as a chimeric flap with vastus lateralis muscle and motor branch of the femoral nerve, it is a viable option for functional reconstructions.